Artificial intelligence in dentistry. Part one. - Makeyev, В. Ф.; Shcherba, П. П. (Actual Dentistry, 2024)
Summary. In recent years, dentistry has undergone a wave of transformations and technological advances, where artificial intelligence has become a driving force that is ready to revolutionize various aspects of oral care. As the world grapples with ever-increasing demand for efficient and personalized medical solutions, artificial intelligence presents itself as a promising ally in the quest to improve diagnostic accuracy, treatment planning and patient care in healthcare system, particularly in dentistry. Purpose: to systematize and review the available data of research information for the period of 2020-2024 regarding the application of artificial intelligence technologies and their use in dental practice for various areas of dental activity. Material and methods. A literature search was conducted on the PubMed service on February 26, 2024. The initial search was carried out using MeSH algorithms: (((«artificial intelligence»[MeSH Terms]) OR («artificial intelligence»[All Fields])) OR («ai»[All Fields])) AND («dentistry»[MeSH Terms]). Publications for the period 2020-2024 were considered. The initial search of the literature included 46 publications. After a detailed analysis of the selected publications, 26 publications, that met the needs, were left for further processing. Also added 6 publications manually, from other services, which disclosed the given topic. Accordingly, the total number of publications used for the analysis was 32 articles. Research results. This research focuses on the growing intersection of artificial intelligence and dentistry with the goal of providing a comprehensive and reasonably up-to-date overview of the various applications, challenges, and opportunities that arise at the intersection of these fields. Through the selected articles, this study aims to explore the impact of artificial intelligence on diagnostic procedures, treatment methods and the overall principle of healthcare delivery using revolutionary technologies. Conclusion. Artificial intelligence is increasingly included in the daily work of dentists, which requires a wider acquaintance with its capabilities in various fields of dentistry.